2009
DOI: 10.1002/jbm.a.32646
|View full text |Cite
|
Sign up to set email alerts
|

In vitro studies on the influence of surface modification of Ni–Ti alloy on human bone cells

Abstract: The in vitro cell behavior on Nitinol after different surface treatments was investigated. As references samples, commercially pure titanium (cpTi) and bioactive titanium were used. The surface treatments influenced the topography, surface energy, crystallographic structure, ion release, chemistry, and ability to form apatite layer from simulated body fluids. Regardless of the surface treatment, the bioactivity study showed that the kinetics of apatite film formation was similar for all tested samples. No clea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 72 publications
1
18
1
Order By: Relevance
“…[26][27][28][29][30][31] In contrary, other studies demonstrated that despite a high nickel surface content and high nickel release rate, cell response was not drastically aected. 1,9,21,32,33 To modulate cell response, simple surface treatments, such as thermal oxidation or polishing, were shown to be as eective as more expensive and complex treatments such as diamond-like coating (DLC).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…[26][27][28][29][30][31] In contrary, other studies demonstrated that despite a high nickel surface content and high nickel release rate, cell response was not drastically aected. 1,9,21,32,33 To modulate cell response, simple surface treatments, such as thermal oxidation or polishing, were shown to be as eective as more expensive and complex treatments such as diamond-like coating (DLC).…”
Section: Introductionmentioning
confidence: 92%
“…[16][17][18][19][20] The manipulation of only surface characteristics, such as local stiness, topography, surface charge, and structure, makes it possible to trigger or inhibit biological action, e.g., cell dierentiation and mineralization. [21][22][23][24][25] Good biocompatibility and/or osseointegration remain a challenge for nickel-titanium. The improvement of the biocompatibility is the primary aim of this article.…”
Section: Introductionmentioning
confidence: 99%
“…The absorbance was measured at 570 nm using BioRadmicroplate reader. 36 Each experiment was performed in triplicate and the average value was statistically represented.…”
Section: Mtt Assaymentioning
confidence: 99%
“…30 However, in previous research, those differentiated cell lineages could also be achieved by applying various chemical differentiation factors, including dexamethasone or other growth factors, such as bone morphogenetic proteins. 31 However, at present, it is valuable to know that topography alone can elicit such effects with sufficient proof. 29 Oh et al noted that the osteoinductive ability of nanotubes on BMMSCs was enhanced as the dimension was increased from 30 nm to 100 nm.…”
Section: Introductionmentioning
confidence: 99%